Analisis Biaya Operasional, Harga dan Kualitas Produk Terhadap Peningkatan Pendapatan Pada UMKM Kuliner di Sidoarjo - Hikmah, Krisila Arini; Supardi, Supardi; Febriansah, Rizky Eka (Jurnal Manajerial, 2024)
Background – Currently, many Micro, Small and Medium Enterprises (MSMEs) in the culinary sector are seeking to capitalize on the widespread appreciation for regional products that are embedded in the cultural fabric of Indonesian society. Likewise, in the Sidoarjo area, a multitude of culinary MSME owners are trying to attract consumers by offering products that offer typical flavors native to their respective regions. Aim – The aim of this research is to determine operational cost tests, price tests and product quality tests to increase the income of MSMEs Design / methodology / approach – This research method is quantitative research with SEM-PLS as a data analysis method with the Smart PLS 3.0 program. Data was collected through a questionnaire distributed to 100 research sample respondents, namely culinary MSMEs in Sidoarjo, with each variable measured using certain statement items. Findings – The findings of this research indicate that culinary MSMEs in Sidoarjo need to focus more on pricing strategies and improving product quality to increase their income. Operational cost efficiency does not necessarily contribute significantly to increasing revenue, possibly because human resources are an obstacle. This research provides important insights for MSME players and stakeholders in formulating effective business strategies, by emphasizing the importance of price and product quality in influencing income. Conclusion - The three variables studied were Operational Costs (X1), Price (X2), and Product Quality (X3), only the Price and Product Quality variables showed a positive and significant impact on Income Increase (Y) among culinary MSME actors in Sidoarjo. Research Implication – This research was carried out to determine whether operational costs incurred could be more effective and have a positive impact on productivity and income. Limitations – Limitations This research only involved the Sidoarjo area